Endoscopically Assisted Middle Cranial Fossa Reconstruction Following Traumatic Intracranial Intrusion of the Mandibular Condyle. Issue 2 (March 2019) - Liau, Isaac; Sambrook, Paul; Cheng, Andrew
Abstract : Abstract: Traumatic intracranial intrusions of the mandibular condyle are a rare injury pattern that carries significant morbid outcomes due to potential for neurological, otological, temporomandibular joint damage, or joint ankylosis. Treatment modalities involve either closed reduction, open approaches via transcranial or subtemporal approaches, or delayed total joint replacement. This paper presents a clinical report of a traumatic intracranial intrusion of the mandibular condyle treated with an endoscopically assisted preauricular approach to reconstruct the middle cranial fossa and temporomandibular articular disc. Endoscopically assisted techniques allow for minimally invasive and less morbid surgical interventions to this pathology, with greater precision than closed reduction techniques.